Prioritizing and aggregating interacting requirements for product-service system development - Zhang, Xinwei; Li, Jing; Eres, Hakki; Zheng, Chen (Expert systems with applications, 2021)
•Requirements prioritization and aggregation are conducted for product-service system (PSS).•Rough-fuzzy DEMATEL is used to determine weights for interacting PSS requirements.•Choquet integral and fuzzy measures are applied to aggregate PSS requirements.•2-order interactions between any two requirements are explicitly modeled.•The method is applied to evaluate requirement interactions for a smart wearable medical system. Requirements evaluation is critically important for the successful development of a product-service system (PSS). The requirements of a PSS often interact with each other, hence significantly influencing requirements evaluation and decision-making processes. The recent literature has proposed some methods such as fuzzy ANP and rough DEMATEL to evaluate interacting PSS requirements and to focus on requirements prioritization. However, aggregation with respect to interacting PSS requirements is seldomly considered. Alternatively, the weighted arithmetic mean method is implicitly used as the aggregation operator to aggregate PSS requirements. Hence, different effects of interactions among any subset of PSS requirements are not considered. This may result in sub-optimal alternatives being adopted for further PSS development. In order to solve this specific problem, a systematic method based on rough-fuzzy DEMATEL, 2-additive fuzzy measures, and the Choquet integral is proposed for aggregating interacting requirements for PSS development along with requirements prioritization. The proposed method utilizes the rough-fuzzy DEMATEL method to determine the weights of interacting PSS requirements when there is a group of experts providing subjective and linguistic assessments of influence strengths. By integrating the Choquet integral with 2-additive fuzzy measures, the proposed method can aggregate interacting PSS requirements non-additively by considering 2-order interactions between any two requirements. To demonstrate its feasibility and advantages, the proposed method is applied to evaluate requirement interactions for a smart wearable medical system.